The Reality of the Primary Schools Principals in Jeddah Practices of Management by Walking Around Remotely from Teachers’ Point of View - Al- Harthi, Maha Safar; Badaoud, Omar Mohammed Omar (Journal of Educational and Psychological Sciences, 2022)
This research study aims to identify the reality of the primary school principals in Jeddah practices of management by walking around remotely from teachers’ point of view. The researcher used the descriptive method to achieve this objective. A questionnaire was created consisting of (33) items and distributed among randomly intended sample consisting of (216) teachers in the primary public education schools of (central Jeddah). The results of the research concluded that the reality of the primary school principals in Jeddah practices of management by walking around remotely from teachers’ point of view gained an overall average (4.18 out of 5), which indicates a (High) degree of practice. At the level of the research dimensions, the dimension of motivation gained the highest average (4.31), then the dimension of improving communication with an average (4.26), and the third dimension of development and creativity with an average (4.21) which all indicated a (Very High) practice. The fourth dimension is feedback, gained an average (4.14), and the fifth dimension is finding the facts that gained an average (4.00), in which both indicated a (High) degree of practice. The researcher presented recommendations and suggestions based on the results above, some of the most important of them are as follows: the inclusion of the concept of management by walking around remotely in the digital education process, designing specialized training courses to develop the practices of school principals for management by walking around remotely, diversifying the motivational methods used in walking around remotely, activating virtual meetings periodically, and making further improvements to distance education programs and adding some features to them; To facilitate the role of the school principal in practicing all dimensions of management by roaming remotely to fulfill the objectives of the remote virtual educational process.